Grand Constantine: a multifunctional peri-urban agriculture for the territorial development of Constantine - Aoulmi, Rima; BOUKERZAZَA Hosni (Journal of Human Sciences, 2021)
The Grand Constantine is a coherent ensemble that represents a regional or even national area of ​​influence that can be a trigger for the territorial development of Constantine in the coming years, through multifunctional periurban agriculture. Possessing wealth to be exploited consisting mainly of land with high agricultural potential, these periurban areas have faced for several decades an anarchic urbanization. Today, agriculture must open up to other horizons because, beyond its primary vocation, it provides benefits to society: it contributes to the attractiveness of territories and landscapes that reflect the image of the city, the management and protection of natural resources, just as it shapes rural landscapes.